Desenvolvimento de cerâmicas refratárias engenheiradas densas e porosas - Pelissari, Pedro Ivo Batistel Galiote Brossi (Universidade Federal de São Carlos, 2019)
High temperature processes are of great importance as they are widely applied in the manufacture of commodities, consumer goods and advanced materials. For these processes to be possible, the thermal environment in which they occur must consist of materials with special features, called refractories, for which their structure at different scales, nano to micro, influence directly their thermal and mechanical performance. The development of high-performance advanced refractory ceramics has been using techniques of theoretical modelling of the materials properties in order to correlate these features, making it possible to improve their performance. This trend is based on the use of computational tools, such as numerical simulation, to evaluate the impact of different structural characteristics on the properties of materials. Thus, the main goal of the present thesis was to use different numerical methods in order to assist the microstructure design of refractory materials for structural and thermal insulation applications. The impact of different microstructural descriptors, such as pore size and distribution, was evaluated for the thermal and mechanical properties of thermal insulating ceramic foams. It was observed the existence of an optimum pore size in the 0.5 to 3.0 m, range which reduces the effective thermal conductivity of these materials to a minimum for temperatures above 1000 °C. In the case of structural materials, it was also developed a bioinspired refractory with engineered microstructure presenting high mechanical performance at room (σf = 672.0 MPa and KIC = 7.4 MPa. m1/2) and high temperature (σf = 350.0 MPa and KIC = 6.0 MPa. m1/2), 1200 °C. The development and characterization of this latest material was carried out in conjunction with the Zurich Federal Institute of Technology (ETHz) and Imperial College London. Additionally, thermo-optical simulations were used to evaluate the thermal performance of these structures for a likely application as thermal barriers.
Development of engineered porous and dense refractories
Keywords: Nacre; Bio-inspired; Thermal insulation; Ceramics; Refractories; Mechanical properties; Bio-inspirado; Cerâmica; Refratários; Propriedades mecânicas; Isolamento térmico; Madre pérola; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS